SISTEM PEMESANAN TEMPAT DI JANTI PARK DENGAN METODE SINGLE CHANNEL-MULTI PHASE - Sakti, Dicky Cahyono; Vulandari, Retno Tri; Widada, Bebas; Kusumaningrum, Andriani (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2024)
Janti Park is a new water attraction that was released at the year 2020. The place is suitable for family gatherings, often many visitors book places for social gatherings, birthdays and meetings. But in the process there are often obstacles in recapping reservations or ordering a place because the system is only via WA and comes directly to Janti Park. To be able to improve service to visitors in booking place, one solution that can be done is to Design a System Web-Based Place Reservation which has the aim of being able to makes it easier for visitors to book a place and no longer need to come to janti park and makes it easier to record reservations for places that have been booked by visitors. In designing this place ordering system using the Single method Channel – Multi Phase with analysis and implementation stages. At the coding stage using web programming languages (HTML, CSS, PHP and). The final results of this research were carried out using black box testing and user acceptance test.